Synthetic Double-Stranded RNA Poly(I:C) Combined with Mucosal Vaccine Protects against Influenza Virus Infection - Ichinohe, Takeshi (American Society for Microbiology, 2005)
The mucosal adjuvant effect of synthetic double-stranded RNA polyriboinosinic polyribocytidylic acid [poly(I:C)] against influenza virus was examined under intranasal coadministration with inactivated hemagglutinin (HA) vaccine in BALB/c mice and was shown to have a protective effect against both nasal-restricted infection and lethal lung infection. Intranasal administration of vaccine from PR8 (H1N1) with poly(I:C) induced a high anti-HA immunoglobulin A (IgA) response in the nasal wash and IgG antibody response in the serum, while vaccination without poly(I:C) induced little response. Intracerebral injection confirmed the safety of poly(I:C). In addition, we demonstrated that administration of poly(I:C) with either A/Beijing (H1N1) or A/Yamagata (H1N1) vaccine conferred complete protection against PR8 challenge in this mouse nasal infection model, suggesting that poly(I:C) possessed cross-protection ability against variant viruses. To investigate the mechanism of the protective effect of poly(I:C), mRNA levels of Toll-like receptors and cytokines were examined in the nasal-associated lymphoid tissue after vaccination or virus challenge. Intranasal administration of HA vaccine with poly(I:C) up-regulated expression of Toll-like receptor 3 and alpha/beta interferons as well as Th1- and Th2-related cytokines. We propose that poly(I:C) is a new effective intranasal adjuvant for influenza virus vaccine.